2022
DOI: 10.3389/fspor.2021.761844
|View full text |Cite
|
Sign up to set email alerts
|

Individuals at Risk of Exercise Addiction Have Higher Scores for Depression, ADHD, and Childhood Trauma

Abstract: BackgroundExercise addiction is increasingly being recognized as a psychologically and physically burdensome set of symptoms. However, little is known about the psychiatric profiles of individuals who are at risk. It is well-established that individuals affected by substance use disorders frequently suffer from depression, attention deficit hyperactivity disorder (ADHD), and experiences of childhood trauma. The aim of this study is to determine whether this pattern of psychiatric disturbance is also present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
(49 reference statements)
3
14
0
Order By: Relevance
“…One investigation found that athletes with EXD had higher likelihood of depression [ t (121) = 4.944, p < 0.001], ADHD [ t (121) = 2.915, p = 0.004], and childhood trauma [ t (121) = 2.297, p = 0.024] [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…One investigation found that athletes with EXD had higher likelihood of depression [ t (121) = 4.944, p < 0.001], ADHD [ t (121) = 2.915, p = 0.004], and childhood trauma [ t (121) = 2.297, p = 0.024] [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this study was to investigate the relationships between ADHD symptomatology with motivation and ED. Based on previous literature [14,15], it was hypothesised that there would be a signi cant positive correlation between ADHD symptomatology and ED. The current ndings support this, as evidenced by the signi cant positive correlation between EDS-T and both ADHD-H and ADHD-T (along with a non-signi cant positive correlation with ADHD-I).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the rate of EA among general exercisers has been found to be around 8.1% [12], rates may be higher in individuals with ADHD. Indeed, there is an established association between ADHD and risk of addictions, including behavioural ones [13], and Colledge et al, [14] found that individuals deemed "at-risk" of exercise addiction reported signi cantly higher symptoms of ADHD. Similarly, Popat et al, [15] found that medicated individuals with ADHD reported higher levels of exercise withdrawal and xation levels, although ED total scores did not differ signi cantly from healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…It is also related to depression, ADHD, and childhood trauma (Colledge et al. 2022 ). Also, individuals who practice extreme mountaineering show higher ratings of self-perceived stress, depression, anxiety, eating disorders, alcohol abuse or dependence, illicit drug abuse, and current and history of psychiatric disorders (Habelt et al.…”
Section: Introductionmentioning
confidence: 99%